Synergistic Interaction of LSAMP Alliances to Improve the Graduation and Transfer of Community College Students in New Jersey United States - San Miguel, Cristiane; Gates, Alexander E (Frontiers in Education, 2021)
The Garden State-LSAMP (GSLSAMP) alliance works collaboratively with the Northern New Jersey-Bridges to the Baccalaureate (NNJB2B) to greatly improve the graduation of community college students from underrepresented minority (URM) groups in STEM and their transfer rate to 4-years STEM programs. This is accomplished through several areas of enrichment. The two alliances sponsor joint activities to encourage a supportive community of 2-years and 4-years students. Community college students conduct research in the labs of mentoring faculty at 4-years programs where they interact with 4-years college students. A cross-campus near-peer mentoring program pairs recently transferred GSLSAMP mentors with mentees from the mentor’s community college of origin that eases and facilitates the graduation and transfer of mentees. In addition, the NNJB2B has adopted five proven high impact practices from GSLSAMP for their students. The results are that the graduation rate of the NNJB2B increased an average of 24.0% annually over the first 5 years of the program and the transfer rate improved 151.0% over the 2012 baseline. Four GSLSAMP 4-years institutions were especially active in the program and experienced an average increase of 62.9% over the 2012 baseline transfers from NNJB2B community colleges.